Integrating Local Wisdom and Character Education in Biology Learning during the COVID-19 Pandemic - Hadi, Khairil; ., Dazrullisa; Susantini, Endang; Kunjtoro, Sunu (KnE Social Sciences, 2023)
Cultural and character issues are problems that must be resolved through education, namely the learning process. Learning today is a shift from traditional learning to online-based learning. These problems can be solved by making innovations in online learning, one of which is by integrating local wisdom and character education. This study aims to determine the integration of local wisdom and character education in online learning-based biology learning. The samples in this study consisted of 20 biology teachers from 20 high schools in West Aceh and Nagan Raya districts. The instruments used were interviews and observation sheets. The data analysis used was qualitative data analysis which consisted of three stages, namely (1) data reduction, (2) data presentation, and (3) concluding. The results showed that the biology teacher in the research sample had integrated local wisdom and character values through assignments, material explanations, and teacher behavior. Biology teachers do not fully understand the understanding of local wisdom and character education so that teachers are still hesitant in making decisions to integrate local wisdom and character values in learning. Keywords: Local wisdom; biology learning; covid-19 pandemic